A long journey to treat epilepsy with the gut microbiota - Li, Qinrui; Gu, Youyu; Liang, Jingjing; Yang, Zhixian; Qin, Jiong (Frontiers in Cellular Neuroscience, 2024)
Epilepsy is a common neurological disorder that affects approximately 10.5 million children worldwide. Around 33% of affected patients exhibit resistance to all available antiseizure medications, but the underlying mechanisms are unknown, and there is no effective treatment. Increasing evidence has shown that an abnormal gut microbiota may be associated with epilepsy. The gut microbiota can influence the function of the brain through multiple pathways, including the neuroendocrine, neuroimmune and autonomic nervous systems. This review discusses the interactions between the central nervous system and gastrointestinal tract (brain-gut axis) and the role of the gut microbiota in the pathogenesis of epilepsy. However, the exact gut microbiota involved in epileptogenesis are unknown, and no consistent results have been obtained based on current research. Moreover, which target should be further explored to identify a novel antiseizure drug is unclear. Most likely, the role of the gut microbiota in epilepsy will ultimately be revealed with the development of genomics technology.